Analyzing nuclear expertise support to population protection decision making process during nuclear emergencies. (January 2018) - Domeneghetti, Bertrand; Benamrane, Yasmine; Wybo, Jean-Luc
Highlights: Analyzing nuclear expertise support to crisis population protection decision making. Data are collected through the observation of four nuclear exercises. Nuclear expertise essential and not enough for population protection decision making. Abstract: Nowadays, strategies to protect population in the early phase of a nuclear crisis consist in three main actions: sheltering, evacuation and iodine pills ingestion. These actions are supposed to be guided by two successive decision-making strategies: triggering reflex actions in pre-planned perimeters in the near field around the accident and then, achieving spatial estimation of doses received by the general public (expressed in Sievert) along the situation development to adapt the actions. Through the observation of four nuclear exercises in France, this paper aims to study the population protection decision making process in the early phase of a severe nuclear accident. This study underlines the existence of a potential intermediate episode in the population protection strategy and how it is currently managed by civilian security and nuclear experts in an emergency situation. We argue that in case of a large nuclear accident, nuclear expertise is essential and not sufficient to take decisions for protecting population.